The match between common antibiotics packaging and guidelines for their use in Australia - Treasure M. McGuire; Jane Smith; Chris Del Mar (Elsevier, 2015)
Abstract Objectives: To determine the potential for a source of surplus antibiotics in the community to come from the mismatch between the recommended duration of antibiotic treatment for common indications in primary care and that dictated by default pharmaceutical industry packaging. Methods: Analysis of existing published information of: 1) the most common antibiotics prescribed in primary care in Australia; 2) their most common indications; 3) the guideline recommendations for their duration; and 4) the duration dictated by antibiotic packaging. Results: Of 32 common antibiotic prescribing scenarios, 10 had doses left over in surplus and 18 had a shortfall, leaving only four in which the packaging size matched the duration recommended by electronic Therapeutic Guidelines. Where there was a shortfall, this was only exactly accommodated by a repeat prescription in two cases. Conclusions: Mismatch contributes to a shortfall or excess of doses compared to recommended antibiotic treatment protocols and probably exaggerates redundant doses in the community from prescribed antibiotics dispensed and not consumed. Implications: Prescribers need to be aware that the mismatch between antibiotic pack sizes and guideline recommendations for their duration is contributing to antibiotic resistance in the community.